2014
DOI: 10.1136/annrheumdis-2013-204838
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality in the antiphospholipid syndrome during a 10-year period: a multicentre prospective study of 1000 patients

Abstract: ObjectivesTo assess the prevalence of the main causes of morbi-mortality in the antiphospholipid syndrome (APS) during a 10-year-follow-up period and to compare the frequency of early manifestations with those that appeared later.MethodsIn 1999, we started an observational study of 1000 APS patients from 13 European countries. All had medical histories documented when entered into the study and were followed prospectively during the ensuing 10 years.Results53.1% of the patients had primary APS, 36.2% had APS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
468
6
31

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 694 publications
(573 citation statements)
references
References 35 publications
28
468
6
31
Order By: Relevance
“…This holds true for treatment of thrombotic APS, where the current mainstay is heparin followed by VKA such as warfarin [6]. Limitations of VKA uses include a narrow therapeutic window, need for repeated monitoring, many food and drug interactions and high variability of response with the need for repeated dose titration.…”
Section: Is Long-term Anti-coagulation An Integral Part Of Treatment mentioning
confidence: 99%
See 2 more Smart Citations
“…This holds true for treatment of thrombotic APS, where the current mainstay is heparin followed by VKA such as warfarin [6]. Limitations of VKA uses include a narrow therapeutic window, need for repeated monitoring, many food and drug interactions and high variability of response with the need for repeated dose titration.…”
Section: Is Long-term Anti-coagulation An Integral Part Of Treatment mentioning
confidence: 99%
“…93 (9.3%) patients died and the most frequent causes of death were severe thrombosis (36.5%) and infections (26.9%). Nine (0.9%) cases of CAPS occurred and 5 (55.6%) of them died [6].…”
Section: Anti-phospholipid Antibodies and Thrombosis In Immune Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, aPL have been reported to be more common in women with stillbirths, recurrent miscarriages, pre-eclampsia and intrauterine growth restriction (IUGR). Approximately 7-25% of unexplained recurrent miscarriage may be due to the presence of aPL (Drakeley et al 1998) along with 3.8% of stillbirths and 13.7% of IUGR (Silver et al 2013, Cervera et al 2015. The reported occurrence of aPL in pre-eclampsia is highly variable, ranging from 11% to 61% (Branch et al 1989, Yasuda et al 1995, Katano et al 1996; however, one group has shown that aPL are one of the strongest maternal risk factors for developing pre-eclampsia, increasing a woman's risk approximately ten-fold (Duckitt & Harrington 2005).…”
Section: Apl and Obstetric Diseasesmentioning
confidence: 99%
“…The presence of these antibodies in pregnant women raises the possibility of obstetric and thrombotic complications [4]. The causal relationship between antiphospholipid antibodies and preeclampsia has not yet been proven [5].…”
mentioning
confidence: 99%